High-speed echoes in the polar winter mesosphere: Infrasound as a probable cause - Belova, Evgenia; Barabash, Victoria; Godin, Oleg A.; Kero, Johan; Näsholm, Sven Peter; Vorobeva, Ekaterina; Le Pichon, Alexis (Advances in Space Research, 2023)
We considered three events on 4 November 2015, 22 December 2016, and 12 November 2018, when the signals travelling in the polar winter mesosphere with high horizontal velocities above 300 m/s were measured by the atmospheric radar ESRAD (Chilson et al., 1999) located at Esrange, near Kiruna in northern Sweden. We proposed four mechanisms of generation of such special cases of polar mesosphere echoes, e.g. high-speed PMWE, that involve microbaroms, i.e. infrasound waves at 0.1 - 0.35 Hz frequencies created by ocean swell. These mechanisms are (i) generation of viscous waves, (ii) generation of thermal waves, (iii) direct contributions of infrasound, and (iv) generation of secondary waves at sound dissipation. These processes necessarily accompany sound propagation in inhomogeneous, thermally conducting and viscous fluid (air). The four models were theoretically analysed and their efficiency was estimated. The infrasound measurements at the IS37 station (Gibbons et al., 2019) located about 170 km north-west from the ESRAD radar, modelled maps of the microbarom sources, infrasound propagation conditions and ionospheric conditions for these three PMWE events support the proposed models. Infrasound-generated thermal waves are suggested to be the most probable specific cause of the observed high-speed, high-aspect-ratio PMWE events. However, absence of in-situ infrasound and plasma measurements did not allow us to quantify contributions of individual physical mechanisms to the fast-travelling echoes generation. Validerad;2023;Nivå 2;2023-11-09 (hanlid); Funder: Research Council of Norway (274377 FRIPRO/FRINATEK); Full text license: CC BY Middle Atmosphere Dynamics: Exploiting Infrasound Using a Multidisciplinary Approach at High Latitudes (MADEIRA)